From ‘artifact’ to stage ‘performance’: A comparison of the romantic-nationalist and performative paradigms in folklore studies - Andalas, Eggy Fajar; Prawiroatmodjo, Sudibyo; Saktimulya, Sri Ratna; Indrastuti, Novi Siti Kussuji (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The emergence of the text/context debate in folklore research has facilitated new interpretations of how researchers approach their objects. Folklore research focusing solely on "text" has faced criticism for disregarding the contextual factors surrounding the genesis of folklore. This study compares the paradigm that perceives folklore textually with the paradigm that contextualizes it by examining the Romantic-nationalist and Performative paradigms. The use of the Romantic nationalism paradigm as a representative of item-oriented research is based on its historical, epistemological, and practical aspects. This study uses a qualitative methodology with a literature review to evaluate and synthesize existing research on the Romantic-nationalist and Performative paradigms in folklore studies. The primary distinction lies in focus: Romantic-nationalism views folklore as a traditional artifact that fosters collective identity, while the performative paradigm sees folklore as a dynamic social event in constant flux. While each paradigm has distinct strengths and limitations, synthesizing both offers a comprehensive perspective encompassing the static and dynamic dimensions of folklore. This study provides a framework for understanding folklore as both cultural heritage and a mechanism for constructing identity within dynamic social change.